POHON KELAPA SEBAGAI MAHAR PERKAWINAN PADA MASYARAKAT WAWONII DI KABUPATEN KONAWE KEPULAUAN - Dauliyah, Syahri; Jamiludin, Jamiludin; Ali Basri, La Ode (Universitas Halu Oleo, 2021)
Abstract: This research aims at analyzing the use of coconut trees as dowry, analyze how to count coconut trees as dowry and change the shape of dowry of coconut trees as marriage dowry in the Wawoni community. The data used are qualitative data. The technique of data collection in this research were observation, interview and documentation. The research method used is a descriptive analysis method that focuses on the interpretation and opinions of informants obtained from interviews and research at the research location and then discussed in the study. The results of the research showed that 1) Coconut trees as a dowry are closely related to natural resources and philosophy in developing households in the Wawonii community, 2) Coconut trees that can be used as the dowry in marriage, namely 1 tree that has been bearing fruit for one puu, a coconut tree that will fruiting the first time talking about 2 trees for 1 puu, a new coconut tree that has a segment on the trunk of 4 trees to escape 1 puu.Â Keywords: coconut tree, dowry, marriage, Wawoni community.